Nekatere topoklimatske značilnosti razporejanja temperature zraka in burje v razgibanem reliefu Slovenije - Ogrin, Darko (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2000)
The paper discusses a problem of distribution of minimum air temperatures in anticyclonic weather conditions and the occurence of temperature inversions in the concave landforms of Slovenia. Analysed in more detail are the conditions in Slovenian Istria where temperature inversions are very explicit in spite of the littoral location, and the conditions on the high Dinaric plateaus where permenent temperature inversion accompanied with inversion of vegetation accur in some of the karst depressions. By applying the method of windshaped trees and actual measurements some topographic characteristics of bora, studied on the profile running from the Trnovski gozd plateau to the sea, are presented in the second part.
Keywords: klimatogeografija; Koprsko primorje; Primorska; relief; Slovenia; Slovenian Littoral; Slovenian Riviera; Slovenija; temperatura; temperaturni obrat; topography; veter; zrak